The Impact Of Antiphospholipid Syndrome On Pregnancy Complications At Different Gestational Stages And The Influence Of Combined Therapeutic Approaches - Ilgarovna, Humbatova Leyla; Sergeevna, Shulcheva Anastasia; Aleksandrovna, Anufrieva Alina; Andreevich, Yudichev Nikita; Ivanovna, Korshunova Arina; Sergeevna, Bryksina Elena; Khoshimzhonovich, Khuzhakulov Dzhonibek; Vladimirovich, Pavlov Bogdan (Journal of Neonatal Surgery, 2025)
The prevalence of antiphospholipid syndrome (APS) varies across different regions of the world, ranging from 1 to 50 cases per 100,000 individuals, with a higher incidence among women compared to men. Pregnancy in women with APS is associated with an increased risk of adverse outcomes, including a higher likelihood of placental insufficiency, preeclampsia, intrauterine growth restriction, miscarriage, stillbirth, and low birth weight relative to gestational age. Antiphospholipid antibodies (aPL) exert their pathogenic effects through multiple mechanisms, including an increase in circulating placental extracellular vesicles that induce endothelial dysfunction; disruption of trophoblast proliferation, differentiation, and apoptosis; mitochondrial DNA release into the cytoplasm, triggering Toll-like receptor activation and sterile inflammation in the placenta; among other pathways. These mechanisms contribute to the detrimental effects of aPL throughout pregnancy. The aim of this review is to examine the impact of APS on all stages of pregnancy and to analyze recent trends in APS management during pregnancy. A review of the literature indicates that lupus anticoagulant (particularly in women with systemic lupus erythematosus) significantly increases the risk of adverse pregnancy outcomes. In other cases, unrelated to systemic lupus erythematosus, pathological effects have been demonstrated for antibodies targeting cardiolipin, β2-glycoprotein I, and phosphatidylserine/prothrombin, which elevate the likelihood of pregnancy complications. The cornerstone of APS treatment during pregnancy is the administration of low-dose aspirin and low-molecular-weight heparin, achieving favorable pregnancy outcomes in 70–80% of cases. The addition of pravastatin or hydroxychloroquine enhances the efficacy of this standard therapy.